Influence of Carcass Fat Iodine Value and Packaging Type on Shelf-life of Bacon Slices Packaged for Hotels, Restaurants, and Institutions (HRI) - A. M. Tapian; B. L. Goehring; J. A. Unruh; B. M. Gerlach; G. D. McCoy; J. M. DeRouchey; R. C. Johnson; S. S. Dritz; J. M. Gonzales; M. J. Matney; T. A. Houser (Kansas Agricultural Experiment Station Research Reports, 2015)
Pork carcasses were selected for fat iodine value (IV) using a NitFom™ sensor. Carcasses were sorted into 3 IV categories, with the target IV range defined as 58 to 63 (low), 68 to 73 (intermediate), and 78 to 83 (high). Seventy-two pork carcasses were identified and bellies collected from both the right and left sides of the carcass for a total of 144 bellies in the study, with 48 bellies (24 carcasses) in each IV category. This experiment had 3 IV treatments, with an average measured carcass IV of 66.5 g/100g (low), 72.6 g/100g (intermediate), and 77.9 g/100g (high) and 2 packaging treatments (aerobic and anaerobic). Fresh bellies were analyzed for dimensional characteristics (weight, length, width, and thickness) and belly firmness. From each belly, 10 sheets of bacon with 7 slices per divider sheet were laid out representing 10 storage dates (d 0, 28 56, 70, 84, 98, 112, 126, 140, and 154) for lipid oxidation analysis. Bacon slices were analyzed for oxidative rancidity and fat color (L* a* b*) for every shelf life storage date. After packaging, bacon slices were stored at 0 ºF for the remainder of the storage period. Day 0 bacon was analyzed for fatty acid composition, pH, and proximate composition. Bacon manufactured from high IV category carcasses had a greater (P<0.05) analyzed IV compared to the intermediate or low IV category, with mean IV values of 76.9, 70.9, and 67.7 g/100g respectively. Belly firmness decreased (P<0.05) as the IV category increased. Bacon slices were not different in proximate composition (fat, moisture, and protein) or pH. High IV bacon samples had greater (P<0.05) percentages of linoleic acid, linolenic, and total polyunsaturated fatty acids; and decreased (P<0.05) percentages of myristic, palmitic, stearic, and total saturated fatty acids compared with the low IV category. Aerobic and anaerobically packaged bacon from the high IV group had lower (P<0.05) L* compared with low IV group. After d 0, aerobically packaged bacon had lower a* values on every sample day through d 154 (P<0.05). Anaerobically packaged bacon had higher a* values on every sample day after d 0 through d 154 (P<0.05). Increasing storage time from d 0 to 154 increased (P<0.05) b* values for both aerobic and anaerobic packaging treatments. Thiobarbituric acid reactive substances (TBARS) did not differ between IV categories. Aerobically packaged bacon had greater (P<0.05) TBARS from d 0 compared to d 28. Thiobarbituric acid reactive substances values were also greater from d 28 to d 154 for aerobically packaged bacon. Thiobarbituric acid reactive substances values for anaerobically packaged bacon did not increase from d 0 to 84. Soluble collagen, insoluble collagen, and total collagen were higher (P<0.05) in the high IV category than the low IV category. No differences were detected in fat cell size or the number of fat cells in bacon fat between IV categories. In conclusion, IV category had minimal impact on frozen bacon quality. However, frozen bacon stored in aerobic packaging resulted in rapid development of lipid oxidation and more pronounced changes in fat color compared with bacon stored in anaerobic packaging.
Keywords: bacon; iodine value; pork